Environmentally friendly products from plants in the control of biodeteriogen agents - Gómez de Saravia, Sandra Gabriela (2013)
Since ancient times, extracts and essential oils from plants "vegetal biocides" have been used as antimicrobials in different fields. Using environ- mentally friendly products is presented as a viable solution that shows advantages from the environmental, economic and ecological standpoint that reduced use of toxic chemicals and pollutants to the environment. The aim of this paper is to present the studies that were used vegetal biocides for the control of microorganisms involved in biodeterioration and that pollute the environment of archives and libraries, and cause human health problems. The "vegetal biocides" were obtained from various plants harvested from natural habitat of La Plata, Argentina and Havana, Cuba. The biocidal activity was studied using the agar diffusion method. Vegetal biocides were analyzed by gas chromatography coupled to mass spectroscopy (GC/MS). The antimicrobial activity is due to sesquiterpe- nes, triterpenoids, flavonoids, sterol, phenols, i.a., and showed moderate effectiveness and/or positive in most vegetal biocides tested.